1991
DOI: 10.1007/bf00056107
|View full text |Cite
|
Sign up to set email alerts
|

Chromomeric organization of polytene chromosomes

Abstract: This is a review summarizing work carried out at the Laboratory of Molecular Cytogenetics in recent years. Problems of genetic organization of bands, interbands and puffs as well as intercalary heterochromatin and position effect variegation are discussed from the point of view of the dynamic model of polytene chromosome organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These studies invariably find that there is an approximately equal number of genes and bands. However, some bands have been found that are multigenic and others have no discernible function (Berendes, 1970;Hochman, 1971;Lefevre, 1974;Young and Judd, 1978;Keppy and Welshons, 1980;Spierer and Spierer, 1983;Zhimulev and Belyaeva, 1991). The idea that each band may represent a single gene is further complicated by the occurrence of overlapping reading frames (Eveleth and Marsh, 1987) and coding regions that reside in the introns of other genes (Henikoff et al, 1986;Chen et al, 1987).…”
mentioning
confidence: 99%
“…These studies invariably find that there is an approximately equal number of genes and bands. However, some bands have been found that are multigenic and others have no discernible function (Berendes, 1970;Hochman, 1971;Lefevre, 1974;Young and Judd, 1978;Keppy and Welshons, 1980;Spierer and Spierer, 1983;Zhimulev and Belyaeva, 1991). The idea that each band may represent a single gene is further complicated by the occurrence of overlapping reading frames (Eveleth and Marsh, 1987) and coding regions that reside in the introns of other genes (Henikoff et al, 1986;Chen et al, 1987).…”
mentioning
confidence: 99%
“…The chromosomes of multicellular animals have a regular and inheritable physical organization. This was first recognized in studies on the lampbrush chromosomes in amphibian oocytes and the polytene chromosomes of insects (Callan, 1963;Nora et al, 2020;Zhimulev and Belyaeva, 1991;Zhimulev et al, 1983). Subsequent research has shown that the architectural features inferred from analysis of lampbrush and polytene chromosomes are present in chromosomes throughout much of the animal kingdom.…”
Section: Introductionmentioning
confidence: 93%